Pelatihan Pengolahan Plastik Limbah Rumah Tangga Menjadi Energi Alternatif - Nugroho, Arif Setyo (ULINA: Jurnal Pengabdian kepada Masyarakat, 2023)
Plastic waste creates problems in the environment. Plastic waste with its properties is difficult to decompose in nature and takes a very long time. This plastic waste ultimately becomes a big problem faced in urban areas and there has been no significant solution to this problem. Some areas flourish with waste banks whose goal is to reduce household waste. The waste bank business group is engaged in managing organic waste and inorganic waste, and inorganic waste is only limited to being sold to collectors. Handling plastic waste in a way that has been developed so far is the 3R principle, namely the principle of reduce, the principle of reuse, and the principle of recycle. But plastic that cannot be processed again with the 3R principle is a problem. The solution is that the plastic waste is processed again using pyrolysis to produce oil that can burn. The results of plastic pyrolysis are oil, and solids in the form of charcoal and gas. Reactor temperature greatly affects the yield, both solids, liquids, and gases. The resulting oil produced from plastic pyrolysis has different characteristics, the higher the pyrolysis temperature the more oil produced but the less solids produced. The color of the oil is also affected by the pyrolysis temperature, the higher the oil temperature the more turbid and becomes wax or wax.